2+6+5+5+5+5+5+5+52+1+2+8+9+1
1+6+5+4+7+8+9+5+5+6+52+2+5+5
1 + 6 + 5 + 4 + 7 + 8 + 9 + 5 + 5 + 6 +52 + 2 + 5 + 5 = 120
1. [ ( -2 ). 3 + 9 ]. ( -5 ) - ( -6 ). 8
2. ( 135 - 35 ). ( -47 ) + 53. ( -48 - 52 )
3. 0 - 1 + 2 - 3 + 4 - 5 + 6 - 7 + ... + 2004 - 2005
4. 1 - 3 + 5 - 7 + 9 - 11 + ... + 2005 - 2007
5.1 + 2 + 3 - 4 - 5 - 6 + 7 + 8 + 9 - 10 - 11 - 12 + ... + 97 + 98 + 99 - 100 - 101 - 102
Tính:
1, 3 1/2 + 4 3/5
2, 3/4 + 6 5/8
3, 5 3/8 + 9 2/7
4, 4 1/2 - 2 3/10
1: =7/2+23/5=35/10+46/10=81/10
2: =6/8+53/8=59/8
3: =43/8+65/7=821/56
Tính:
1, 3 1/2 + 4 3/5
2, 3/4 + 6 5/8
3, 5 3/8 + 9 2/7
4, 4 1/2 - 2 3/10
\(a,3\dfrac{1}{2}+4\dfrac{3}{5}=\dfrac{81}{10}\\ b,\dfrac{3}{4}+6\dfrac{5}{8}=\dfrac{59}{8}\\ 5\dfrac{3}{8}+9\dfrac{2}{7}=\dfrac{821}{56}\\ 4,4\dfrac{1}{2}-2\dfrac{3}{10}=\dfrac{11}{5}\)
1-2-2-1-2-1-2-1-2-1--45-4356-42-------32423432---5-45-54535-435-34-5-35-2-5-4-52-5-54-353--3-5--5-34-5-3--4-47-87-8-787-9-76-8--34-54-6----34-3-31-4-31-423-34-1-134-41-4232-431-321------------546-3----------------2315-413-513465146-456-4-164-316361-4363411111111111111=
-4.3634111e+18
HT
@acquybemon
-5/8 - 7/1
-8/28-15/27
-1/39+ -1/52
-6/9 + -12/16
-2/5 - -3/11
Tính nhẩm:
8 + 1 = … | 7 – 5 = … | 5 + 2 = … | 10 – 6 = … |
28 + 1 = … | 57 – 5 = … | 7 – 35 = … | 52 + 0 = … |
45 + 2 = … | 49 – 6 = … | 7 – 2 = … | 99 – 8 = … |
Lời giải chi tiết:
8 + 1 = 9 | 7 – 5 = 2 | 5 + 2 = 37 | 10 – 6 = 4 |
28 + 1 = 29 | 57 – 5 = 52 | 7 – 35 = 2 | 52 + 0 = 52 |
45 + 2 = 47 | 49 – 6 = 43 | 7 – 2 = 35 | 99 – 8 = 91 |
8+1=9
7-5=2
5+2=7
10-6=4
28+1=29
57-5=52
7-35=-28
52+0=52
OKKKKKKKKKKKKKKKKKKKKKKKKKKKKKKKKKKKKKKK
1) |2x - 1| = 5
2) |2x - 1| = |x + 5|
3) |3x + 1| = x - 2
4) |3 - 2x| = x + 2
5) |2x - 1| = 5 - x
6) |- 3x| = x - 2
7) |2 - 3x| = 2x + 1
8) |2x - 1| + |4x ^ 2 - 1| = 0
9) (2x + 5)/(x + 3) + 1 = 4/(x ^ 2 + 2x - 3) - (3x - 1)/(1 - x)
10) (x - 1)/(x + 3) - x/(x - 3) = (7x - 3)/(9 - x ^ 2)
11) 5 + 96/(x ^ 2 - 16) = (2x - 1)/(x + 4) + (3x - 1)/(x - 4)
12) (2x)/(2x - 1) + x/(2x + 1) = 1 + 4/((2x - 1)(2x + 1))
13) (x + 2)/(x - 2) - 1/x = 2/(x ^ 2 - 2x)
14) x/(2x - 6) + x/(2x + 2) = (2x + 4)/(x ^ 2 - 2x - 3)